EMPHASIS ENTREPRENEURIAL COMPETENCIES AND ETHICS FOR GLOBAL SUSTAINABILITY: (AT THE INTERNATIONAL CONFERENCE OF LAMAPPAPOLEONRO UNIVERSITY) - Wahyulis Hersya; Mislah Fakhira Nisa; Febriyanti Nur; Puji Rahma; M Afdal Tahir (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
This abstract was presented at the international conference of Lamappapoleonro University, themed "Excellent And Professional Entrepreneurship For Global Sustainability," conducted via Zoom on October 13, 2025, at 1:30 PM. The speakers were scholars from several universities in India, Pakistan, Malaysia, Thailand, and Uzbekistan. This study analyzes how entrepreneurial skills and ethics affect global sustainability goals. Entrepreneurship is seen as a key driver of economic growth and sustainability in the face of climate change, social inequality, and environmental degradation. This study outlines the core competencies and ethics that promote sustainable business growth and professional entrepreneurship.  The qualitative study interviewed 15 successful entrepreneurs from Asia, Europe, and Africa who have integrated sustainability into their businesses. The findings emphasize the need of ethical decision-making, long-term thinking, and stakeholder engagement in company strategies. These attributes lead entrepreneurs to make more expensive but beneficial social and environmental decisions. This research illuminates the relationship between professional entrepreneurship and global sustainability activities, influencing educational curriculum and company operations. To achieve sustainable growth, entrepreneurial skills and ethics are needed, according to study. The data show that entrepreneurial greatness includes integrity, social responsibility, and environmental care as well as financial success.